2015
DOI: 10.1111/pedi.12351
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes in very young children: a model of parent and child influences on management and outcomes

Abstract: The incidence of type 1 diabetes (T1D) in very young children (YC-T1D) is increasing globally. Managing YC-T1D is challenging from both a medical and psychosocial perspective during this vulnerable developmental period when complete dependence upon parental caretaking is normative and child behavior is unpredictable. The consequences of suboptimal glycemic control during this age range are substantial since these children will have T1D for many years and they are prone to adverse neuropsychological sequelae. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 69 publications
2
39
0
Order By: Relevance
“…Previous studies have demonstrated an improvement in metabolic control following participation in residential diabetes camps . Our observations are consistent with prior studies as well as a recently proposed model associating individual parent and child characteristics with management behaviors and glycemic outcomes of T1DM in young children . Our study adds to the existing literature by confirming the beneficial effects of a residential family‐based camp experience in a younger population of children.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous studies have demonstrated an improvement in metabolic control following participation in residential diabetes camps . Our observations are consistent with prior studies as well as a recently proposed model associating individual parent and child characteristics with management behaviors and glycemic outcomes of T1DM in young children . Our study adds to the existing literature by confirming the beneficial effects of a residential family‐based camp experience in a younger population of children.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of T1DM among children under 5 years of age is rapidly increasing . Behavioral challenges that are common among young children, including mealtime and bedtime habits, can be exacerbated in young children with T1DM, yielding significant parental distress and poor glycemic control . Psychological stress related to caring for a child with T1DM can compromise parental coping and negatively impact parental well‐being, which in turn may affect their diabetes‐related parenting tasks .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, parents of children with T1D need to balance performing T1D management required to achieve near‐normal glycemic control with teaching their child age‐appropriate T1D self‐care in a way that promotes child's competence and future independence. This suggests that parental involvement as well as, the manner in which parents interact with their child when completing T1D management tasks may influence short‐ and long‐term glycemic control . In parents of children newly diagnosed with T1D, this balancing act is even more complicated as parents themselves are learning daily T1D self‐care while teaching their child about his or her own T1D self‐care …”
Section: Introductionmentioning
confidence: 99%
“…This suggests that parental involvement as well as, the manner in which parents interact with their child when completing T1D management tasks may influence short-and long-term glycemic control. 5 In parents of children newly diagnosed with T1D, this balancing act is even more complicated as parents themselves are learning daily T1D self-care while teaching their child about his or her own T1D self-care. 6 Parenting style describes how parents interact with their child.…”
Section: Introductionmentioning
confidence: 99%